Preliminary study on screening and selection of Lactic Acid Bacteria (LAB) from gastrointestinal tract of naleh fish (Barbonymus sp.) - Yulvizar Cut; Yunita Dewi; A Muchlizin Zainal; Suhartono Suhartono (BIO Web of Conferences)
The naleh fish (Barbonymus sp.) is an indigenous species found in Nagan Raya Regency, Aceh Province. The presence of Lactic Acid Bacteria (LAB) in the gastrointestinal tract of the fish may potentially act as probiotics, thus promoting the growth of the naleh fish. The objective of this research is to isolate, characterise and select LAB through physiological testing. The research was conducted using a purposive sampling survey method and isolated the bacteria on selective media, namely Man, Rogosa, Sharpe (MRS) agar. The selection of physiological tests conducted included catalase tests, tests of the ability of the bacteria to survive at different temperatures, and tests of the effect of varying concentrations of NaCl. The research findings identified seven isolates with different colony characteristics of LAB. The morphology of the colonies was observed is punctiform (57.14%) and circular (42.85%). The colour is cream (14.28%) and white (85.71%). The edges were noted to be smooth (100%) and the elevation was observed to be flat (100%). The cell morphology is coccus - shaped (100%) and the bacteria are classified as Gram staining positive (100%). The growth of all LAB isolates from the gastrointestinal tract of the naleh fish is can survive by differences in temperature, NaCl concentration and catalase negative test.